2016
DOI: 10.1007/978-3-319-45823-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Feature Based Algorithm Configuration: A Case Study with Differential Evolution

Abstract: International audienceAlgorithm Configuration is still an intricate problem especially in the continuous black box optimization domain. This paper empirically investigates the relationship between continuous problem features (measuring different problem characteristics) and the best parameter configuration of a given stochastic algorithm over a bench of test functions — namely here, the original version of Differential Evolution over the BBOB test bench. This is achieved by learning an empirical performance mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…There are a number of avenues to investigate, discussed above, which may improve the methodology further. In particular an investigation into more sophisticated function features, such as those used in FBAC [3], is a high priority. The long term goal should be to extend this methodology to automatically select the most appropriate evolutionary algorithm for a problem, not just the control parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of avenues to investigate, discussed above, which may improve the methodology further. In particular an investigation into more sophisticated function features, such as those used in FBAC [3], is a high priority. The long term goal should be to extend this methodology to automatically select the most appropriate evolutionary algorithm for a problem, not just the control parameters.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of metrics which can be utilised to define the performance of an optimisation algorithm [7,3]. The meaning of performance may change depending on the application [13], but in general we wish to reduce the objective function value with a small number of objective function evaluations.…”
Section: Optimisation Algorithm Performance Metricmentioning
confidence: 99%
“…The per-instance variant of the algorithm configuration problem, which can be seen as a generalisation of per-instance algorithm selection, largely remains an open challenge (see, e.g., Hutter et al, 2006;Belkhir et al, 2016Belkhir et al, , 2017, and we briefly discuss it further in Section 6.…”
Section: Algorithm Selection and Related Problemsmentioning
confidence: 99%
“…Note that by using a platform-independent web-application of the flacco package 1 (Hanster and Kerschke, 2017), researchers and practitioners, who are unfamiliar with R, can also benefit from this extensive collection of more than 300 landscape features. Belkhir et al (2016Belkhir et al ( , 2017 were among the first to leverage the ELA features provided by flacco for per-instance algorithm configuration.…”
Section: Continuous Problemsmentioning
confidence: 99%
“…In contrast to [18], Muñoz et al [26], the empirical performance model was learned by using a multi-layer neural network method. More recently, based on aforementionned features in Section 4, Belkhir et al [5] investigated the PIAC on Differential Evolution [29], by considering different sets of features and a discretization of the parameter space (≈ 8000 parameter configurations. According to [18], an empirical performance model is learned with a Random Forest regression, and based on a cross-validation procedure where each test function of the BBOB test were removed one at a time, Belkhir et al [5] empirically demonstrated that predicted parameter setting found with PIAC can outperform a robust parameter setting, and approach the best parameter setting, whereas remains outperformed by a specialized parameter setting found with an AC method like SMAC.…”
Section: Piac In Continuous Domainmentioning
confidence: 99%